2018
DOI: 10.4315/0362-028x.jfp-17-347
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Methodology for Salmonella Inactivation during Extrusion Processing of Oat Flour

Abstract: An increase in the number of foodborne outbreaks and recalls due to Salmonella in low-moisture foods has resulted in the need for the development and validation of process controls to ensure their microbiological safety. Furthermore, the Food Safety Modernization Act Preventive Controls for Human Food final rule requires food processors to validate their process controls to ensure food safety. The objective of this study was to develop a response surface model to predict Salmonella inactivation in oat flour, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…The study done here had a slightly higher temperature range (75 to 95 °C), which resulted in a slightly higher moisture loss (1.0% to 3.0%). These results are also in agreement with the study done by Verma et al (), which reported a loss of 1.5% to 2.5% moisture during extrusion at similar conditions to those reported here. In industrial applications moisture losses obtained by flash‐off as hot products expand at the die during the extrusion may be as high as 4.0% to 7.0%.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…The study done here had a slightly higher temperature range (75 to 95 °C), which resulted in a slightly higher moisture loss (1.0% to 3.0%). These results are also in agreement with the study done by Verma et al (), which reported a loss of 1.5% to 2.5% moisture during extrusion at similar conditions to those reported here. In industrial applications moisture losses obtained by flash‐off as hot products expand at the die during the extrusion may be as high as 4.0% to 7.0%.…”
Section: Resultssupporting
confidence: 94%
“…In industrial applications moisture losses obtained by flash‐off as hot products expand at the die during the extrusion may be as high as 4.0% to 7.0%. At different fat levels (5%, 10%, and 15%), the water activity of the samples ranged from 0.70 to 0.95 for various moisture content (14% to 26% wb) at room temperature (Verma et al ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations